Interferon alpha (IFN-α) in systemic lupus erythematosus (SLE) - Sara Moqbil; Eryk Mikos; Joanna Dmochowska; Aleksandra Wójcik; Milena Leziak (Kazimierz Wielki University, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown etiology. An important role in the pathogenesis of SLE has been attributed to interferon alpha (IFN-α), which stimulates the expression of numerous genes, resulting in an increased autoinflammatory response. Recent studies have demonstrated  increased levels of this cytokine in patients with SLE, as well as in relatives, indicating that IFN- α is an inherited risk factor for lupus. Cases of induction of SLE/lupus-like syndrome after IFN- α therapy also point to the involvement of interferon in the pathogenesis of the disease. Interferon being a probable initiator of the disease, as well as a marker to examine its exacerbations, is a potential research target to better understand the etiology and pathogenesis of lupus. More research is needed to determine the feasibility of using INF-blocking agents for new therapies in SLE.